Monitoring of environmental education program in urban nature reserve "Bosque Autóctono El Espinal" - Evangelina Natale; Carola Astudillo; Antonia Josefina Oggero (Universidad de Costa Rica, 2017)
The Urban Natural Reserve "Bosque Autóctono El Espinal" has undertaken the design and implementation of an Environmental Education Program destined to the educational community aiming for the re-signification of the Urban Natural Reserves as complementary areas for learning ("open-air classrooms"). The program is based on the elaboration of activities that help to understand the local natural settings and their main environmental problems in a significant, active and committed manner. All these activities were differentiated according to the potential audience by setting different levels for contents, thinking processes, language and technical vocabulary. To monitor the experience, teachers, students and interpreters were subjected to interviews, and information from field work was registered. All these instruments were implemented before, during and after the visits; 141 cases were analyzed. In general, both the informative materials and the collections and samples were not only easy to comprehend but also attractive for the visitors, and the implemented modality particularly favored interaction, dialog and the spontaneous expression among visitors. The activities provided a good opportunity for the discussion of real problems. Moreover, the post-visit productions allowed us to recognize new learnings in the students, who were able to acknowledge distinctive characters of native biodiversity and the important role of the protected areas. We can assure that these areas complement school learning with life experiences, giving new signification to the official curricula for the local and current environmental problems. The results obtained gave rise to recommendations for the methodological adjustment of new experiences. La Reserva Natural Urbana "Bosque Autóctono el Espinal" (Córdoba) se ha abocado al diseño e implementación de un programa de Educación Ambiental destinado a la comunidad educativa regional. La meta  de dicho programa es incluir y resignificar estos espacios como ámbitos complementarios para el aprendizaje ("aulas a cielo abierto") mediante del diseño de materiales y actividades para la comprensión significativa, activa y comprometida del medio natural local y de sus principales problemáticas ambientales. Estas actividades se diferenciaron en función de públicos potenciales, con lo cual se delimitaron  los niveles de complejidad en cuanto a contenidos, procesos de pensamiento y vocabulario técnico. Se realizó un monitoreo de la experiencia mediante encuestas y entrevistas a docentes, estudiantes e intérpretes, así como registros a campo. Estos instrumentos de recolección de datos fueron implementados antes, durante y después de las visitas. En total se analizaron141 casos y en términos generales, tanto los materiales informativos como colecciones y muestras resultaron no solo comprensibles, sino también atractivos para los visitantes, mientras que la modalidad implementada favoreció especialmente la interactividad, el diálogo y la expresión espontánea de los visitantes. Asimismo, las actividades ofrecieron espacios para la discusión de problemas reales, al referir a la interacción de diferentes variables del contexto. Además, las producciones post-visita permitieron reconocer nuevos aprendizajes en los estudiantes, quienes lograron dar cuenta de caracteres propios de la biodiversidad nativa y de la  importancia de las áreas protegidas. Finalmente, podemos afirmar que estos espacios complementan los aprendizajes escolares con experiencias vivenciales, con ello se resignifican los contenidos de la curricula oficial en torno a problemáticas ambientales locales y actuales.